Influence of social media influencers and testimonials on consumer attitudes and purchase decisions for Scarlett Whitening products - Vhiona Mayari Tandela; Rahmad Rahmad; Irvan Adi Girsang; Crisda Emeliana Girsang; Aldini Syahputri (Digital Business: Tren Bisnis Masa Depan, 2023)
Product marketing through influencers on social media is a new phenomenon in the marketing industry. Therefore, marketing through social media is carried out by a company to reach a certain target market through people who have great influence on social media or are called influencers. These influencers are adjusted to the values of the product to be marketed in order to find suitable potential customers. Influencers will also provide new information and demonstrate their skills to influence consumer attitudes or behavior in making purchasing decisions. Apart from influencers, there are also testimonials that are used to attract customers to make a decision before making a purchase. These testimonials are real evidence shared by consumers who have felt satisfied or disappointed with the products or services they bought on social media. The method used in this study is data collection in the form of a questionnaire given to 56 respondents by providing structured questions, and using variable data, namely data on the dependent variable (Y) and the independent variable (X). The results of data processing obtained from 56 respondents who are USI economics students who use social media, it can be concluded that social media influencers and testimonials of a beauty product called Scarlett Whitening are quite significant in influencing consumer behavior and determining consumer satisfaction. Because the results of the percentage of answer scores that each indicator have are in the strong category, namely 3.24% for the influencer variable, 2.98% for the testimonial variable, and 3.23% for the consumer behavior variable.